37.3k views
3 votes
F(x)=√x + 7,
f-¹(x).

User Gaohomway
by
6.2k points

1 Answer

3 votes

Answer:

f⁻¹(x) = (x - 7)²

Explanation:

f(x) = √x + 7

Steps to follow to find inverse function:

  • Replace f(x) with y.

y = √x + 7

  • Replace every x with y and replace every y with x.

x = √y +7

  • Now, solve the above equation for 'y'.

x = √y + 7

Subtract 7 from both sides,

x - 7 = √y

Square both sides,

(x - 7)² = y

Now, inverse function, f⁻¹(x) = (x - 7)²

User Bruno BEAUFILS
by
5.3k points